EFFET DU BARRAGE HYDROELECTRIQUE RUZIZI I SUR LA TURBIDITE DES EAUX, L’ENVASEMENT DU RESERVOIR ET LE TRANSPORT DES MATIERES EN SUSPENSION - Augustin, NDIWAMUNGU BADERHAGE (IJRDO - Journal of Social Science and Humanities Research, 2023)
This study was carried out over a period from January 2018 to June 2018 and focused on the effect of the Ruzizi I hydroelectric dam on water turbidity, reservoir siltation and transport of suspended matter. The main objective was to evaluate by turbidimetry the effect of the dam on the flow of suspended solids and the rate of siltation of the reservoir of the Ruzizi I hydroelectric power plant in a context of strong anthropization prevailing in the watershed of this ecosystem. The results showed that the waters of the Ruzizi River both upstream and downstream are disturbed in the rainy season and much more upstream due to muddy waters from the watershed constantly subject to erosion. The waters at these sites are highly oxygenated and aerated, low oxygen levels are associated with increased siltation rates and turbidity. Hydrology showed that the reservoir of the plant is almost dependent on Lake Kivu, the relationship between the water level of the Ruzizi I reservoir and that of Lake Kivu being a linear function where precipitation does not immediately show consequences on the water level and turbine flows. The suspended solids concentrations of the reservoir and the outlet of the dam are respectively 9.1 and 5.9 mg/l, i.e. a difference of 3.2 mg/l. It therefore turns out that 64.8% of the flow of suspended solids is transported through the turbine and 35.2% of the quantity received at the level of the reservoir is retained by the dam. Considering an average flow of 97.2 m3/s, a flow of 573.48 g/s or 49.5 tons per day of suspended particles is established through the dam, or an equivalent of 18.080 kilotons per year. Thus, the load of 35.2% of the particles retained corresponds to a sedimentary deposit of 26.9 tons per day, i.e. an equivalent of 9.8 kilotons per year of siltation. The residual concentration of 3.2 mg/l of Suspended Solids, MES in a tank of 146,104 m3 of water represents a residual particle load of 4,672 tons. A significant number of anthropogenic activities accelerate siltation and increase the turbidity of watercourses and a negative effect on the Ruzizi I dam.